Intrinsic motivation as a determinant of perceived usefulness of library makerspace: the influence of learning dimensions - Haruna, Bala; Kiran K. (Malaysian Journal of Library and Information Science, 2023)
An increasing number of academic libraries are providing techno-savvy spaces, generally regarded as makerspace, that plays a significant role to serve the learning needs of university students. Yet, the underutilization of these makerspaces among learners in Nigerian universities is a growing concern. This study suggests a model using the Self-Determination Theory and the Tinkering Learning Dimensions Framework to investigate the influence of intrinsic motivation and learning dimensions (learning engagement and social scaffolding) on the perceived usefulness of library makerspace among Nigerian university students. Using a quantitative approach, four hypotheses were developed to examine the relationship between the constructs. Data from 323 valid respondents were analyzed using structural equation modeling. The findings reveal that intrinsic motivational factors have no direct statistically significant influence on the perceived usefulness of library makerspace. However, the relationship is mediated by an indirect influence of learning engagement. Social scaffolding and learning engagement were both found to have a direct significant influence on the perceived usefulness of makerspace. This study contributes to understanding the factors that influence the perceived usefulness of makerspace which would then lead to the increased use of this collaborative workspace. Contribution to the literature of the utilization of makerspace is discussed based on the presented framework.